Fostering Independent Learning in Early Childhood: A Case Study on Montessori Pedagogy at PAUD Montessori Futura Indonesia - Qadafi, Muammar; Maulidya Ulfah; Miftachul Huda; Agustiningsih, Neneng (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2023)
The primary objective of this research is to assess the effectiveness of Montessori pedagogy in nurturing independent learning in early childhood education, specifically at PAUD Montessori Futura Indonesia. Utilizing a descriptive case study approach, the study examines daily routines, learning activities, and the role of educators in fostering independence. The findings indicate that children consistently engage in independent behaviors, such as choosing activities autonomously and requiring minimal teacher intervention. Educators are instrumental in crafting activities that bolster independent learning, and the learning facilities are strategically organized to facilitate this objective. The practice of age grouping within the institution further enriches the learning environment by instilling a sense of responsibility among older children. These outcomes have considerable implications for both research and practice in early childhood education, suggesting that Montessori pedagogy can effectively promote independent learning. However, the study is confined to a single educational setting and does not explore the Montessori approach's long-term effects or adaptability in diverse socio-cultural contexts. Future research is recommended to investigate these areas for a more holistic understanding of the efficacy of Montessori pedagogy in promoting independent learning.